2021
DOI: 10.3390/atmos12030337
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Distribution and Gas/Particle Partitioning of Polycyclic Aromatic Hydrocarbons (PAHs) in the Atmosphere of Strasbourg, France

Abstract: Gas and particulate phase ambient air concentrations of polycyclic aromatic hydrocarbons (Ʃ16PAHs) were determined in Strasbourg, a large city located in the Alsace region of northeastern France, from May 2018 to March 2020, to study the evolution of their temporal variations and their potential origins. The analysis of PAHs was performed using a global analytical method permitting the quantification of pesticides, PAHs, and polychlorobiphenyls (PCBs). Filters and Carbon doped silicon carbide NMC@SiC foams wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…These results suggest photodegradation processes of PAHs in the particulate phase by ozone that could significantly affect PAH transformations, especially during summer and spring, when concentrations of O 3 are high (mean = 76.3 and 66.8 µg m −3 , respectively) 29 . Similar photochemical effects of ozone on particulate PAHs during the warm study period have been demonstrated in previous studies 13 , 15 , 16 , 49 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…These results suggest photodegradation processes of PAHs in the particulate phase by ozone that could significantly affect PAH transformations, especially during summer and spring, when concentrations of O 3 are high (mean = 76.3 and 66.8 µg m −3 , respectively) 29 . Similar photochemical effects of ozone on particulate PAHs during the warm study period have been demonstrated in previous studies 13 , 15 , 16 , 49 .…”
Section: Resultssupporting
confidence: 89%
“…In this study, the BaP/BghiP ratio was more than 2 times higher during the cold season compared to the warm one. Therefore, vehicular exhaust emission is expected to play an important role in high-molecular-weight PAH pools, depending on season and meteorological conditions, as observed in many previous studies 4 , 6 , 7 , 11 , 49 .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, gaseous PAHs produced by primary emissions (i.e., vehicle emission and fuel evaporation) might be photo-oxidized and react with various high-potential oxidants (i.e., ozone, nitrate radical, and hydroxyl radical) in the atmosphere. Therefore, the difference in high traffic congestion could be the reason for the significant reactivity of those compounds because of widely detected gaseous PAH concentrations [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found two- to three-ring PAHs are a gaseous phase, while five- to seven-ring PAHs are a particulate phase. However, both phases are found in four-ring PAHs [ 7 , 8 , 9 ]. Although gaseous PAHs are less carcinogenic/mutagenic, there are many in the atmosphere and they can interact with other pollutants to produce derivatives through processes such as sulfonation, nitration, and photo-oxidation [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%